A rodent version of the Iowa Gambling Task: 7 years of progress - Van Den Bos, Ruud; Koot, Susanne; de Visser, Leonie (Frontiers in Psychology, 2014)
In the Iowa Gambling Task (IGT) subjects need to find a way to earn money in a context of variable wins and losses, conflicting short-term and long-term pay-off, and uncertainty of outcomes. In 2006, we published the first rodent version of the IGT (r-IGT; Behavior Research Methods 38, 470-478). Here, we discuss emerging ideas on the involvement of different prefrontal-striatal networks in task-progression in the r-IGT, as revealed by our studies thus far. The emotional system, encompassing, among others, the orbitofrontal cortex, infralimbic cortex and nucleus accumbens (shell and core area), may be involved in assessing and anticipating the value of different options in the early stages of the task, i.e. as animals explore and learn task contingencies. The cognitive control system, encompassing, among others, the prelimbic cortex and dorsomedial striatum, may be involved in instrumental goal-directed behaviour in later stages of the task, i.e. as behaviour towards long-term options is strengthened (reinforced) and behaviour towards long-term poor options is weakened (punished). In addition, we suggest two directions for future research: (1) the role of the internal state of the subject in decision-making, and (2) studying differences in task-related costs. Overall, our studies have contributed to understanding the interaction between the emotional system and cognitive control system as crucial to navigating human and non-human animals alike through a world of variable wins and losses, conflicting short-term and long-term pay-offs, and uncertainty of outcomes.